STRUCTURE AND HARDNESS OF CASTINGS MADE FROM WEAR-RESISTANT CAST IRON - E. I. Marukovich; V. M. Ilyushenko; P. Yu. Duvalau; A. I. Kalentsionak; K. E. Baranouski (Литьë и металлургия, 2017)
Influence of ways of casting and influence of geometrical parameters of details made from chromic cast irons on hardness of their inner layers are investigated. The technique of researches is developed and experiments are made. Compliance of details from chromic cast irons to performance specification by hardness is determined. The microstructure analysis on the section of details is carried out.